2015
DOI: 10.4238/2015.august.28.10
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor (CAG)n polymorphisms and breast cancer risk in a Han Chinese population

Abstract: ABSTRACT. The androgen receptor (AR) is involved in the differentiation and growth of breast cancer. Genetic markers in the AR gene have a plausible role in modulating the risk of breast cancer. In this study, we studied the association of breast cancer and the trinucleotide repeat polymorphism (CAG)n in exon 1 of the AR gene in 202 patients with breast cancer and 183 healthy controls from our hospital (Yinchuan, China). Repeat lengths were determined by fluorescent DNA fragment analysis using the ABI GeneScan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The abnormal range of CAG repeat length is usually associated with the risk of developing different cancer types including ovarian cancer (7)(8)(9)(10)(11). However, previous studies of the association between AR CAG repeat polymorphism and ovarian cancer risk have shown inconsistent results (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The abnormal range of CAG repeat length is usually associated with the risk of developing different cancer types including ovarian cancer (7)(8)(9)(10)(11). However, previous studies of the association between AR CAG repeat polymorphism and ovarian cancer risk have shown inconsistent results (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 87%
“…It is reported that different ethnicities have different CAG repeat lengths, with the shortest being reported in African-Americans (mean,20; range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and the longest in Mexican-Americans (mean,25; range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (6). Studies have shown that CAG repeat lengths were associated with the risks of different cancer types in various populations, such as breast cancer, prostate cancer and colorectal cancer (7)(8)(9). In terms of ovarian cancer, some studies have shown that long CAG repeat allele was associated with increased ovarian cancer risk (10,11), while other studies have reported an inverse association between CAG repeat length and ovarian cancer risk (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Asian women, there is a link between shorter CAG repeats and a higher risk of developing epithelial ovarian cancer [254]. In contrast, longer CAG repeats are present at a higher frequency in breast cancer patients of the Han Chinese population [82]. Although the CAG repeat length does not affect prostate cancer risk amongst European men, carriers of the SNP rs1204038A allele are more likely to develop this cancer [21].…”
Section: Disparities At the Nuclear Genome Level And Their Role Inmentioning
confidence: 99%
“…As a result, studies on the polymorphism of CAG repeat numbers on the AR gene have attracted wide research interest recently. The correlations between the repeat numbers and several diseases such as MAGA, acne, prostate cancer, hypertrichosis, and breast cancer have been established [12,13,14,15,16,17,18]. Thus, we sought to investigate the correlation between the CAG repeat numbers on the AR gene and FPHL in a Han Chinese population.…”
Section: Introductionmentioning
confidence: 99%